BRAZILIAN DEMOCRATIC RULE OF LAW AND THE CITIZEN CONSTITUTION: STRUCTURE, CHALLENGES AND PERSPECTIVES (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
This article examines the challenges faced by the Democratic State of Law in Brazil, highlighting the importance of the 1988 Citizen Constitution, the fundamental rights it upholds, and the current threats to democracy. Through an analysis of popular participation and constitutional guarantees, the study discusses how the Constitution ensures individual and collective rights, as well as the need for protection against setbacks and violations. The study also addresses the implications of antidemocratic attitudes and the role of the Penal Code in preserving the democratic regime. The methodology used will be a review: both bibliographic and normative on the subject. Additionally, a case study will be conducted specifically on the antidemocratic acts against Congress, the Presidential Palace, and the Federal Supreme Court on January 8, 2023, which are considered political crimes, in order to demonstrate the current state of the art on the topic. It is concluded that raising public awareness about the importance of following a progressive and positivist path is fundamental for the preservation of democracy, ensuring respect for the principle of human dignity and fundamental and social rights, thus promoting the fullness of Brazilian citizenship.